Utilization of Original Texts in Kitabah to Motivate and Develop Arabic Writing Skills - Harahap, Fitri Handayani; Mimantasyah, Virza; Salsabilla, Salwa; Putri, Rahma Dwi; Nasution, Sahkholid (Holistic Science, 2025)
Arabic writing instruction (kitabah) is often considered difficult by students due to conventional teaching methods that tend to be rigid and non-contextual. This study aims to examine the implementation of authentic content-based writing instruction as an effort to enhance students’ motivation and Arabic writing skills. The research employed a quantitative approach with a quasi-experimental design, involving two groups of students: experimental and control. The experimental group received instruction using authentic materials such as news articles, advertisements, and social media dialogues, while the control group continued with traditional methods. Findings revealed a significant improvement in writing ability and learning motivation among students in the experimental group. Authentic content was proven to create more relevant, interactive, and meaningful learning experiences, helping students understand the practical use of Arabic in real-life contexts. Therefore, this instructional strategy is recommended for broader implementation in Arabic language curricula at secondary and tertiary educational levels.